경피적 척추성형술, 또는 경피적 풍선 척추성형술 시행 후 발생한 추체의 재압박과 시멘트 형상과의 상관관계 및 재압박 유발 위험인자에 대한 분석 - 전득수(Deuk Soo Jun); 백종민(Jong Min Baik); 윤영현(Young Hyun Yoon) (The journal of the Korean Orthopaedic Association, 2022)
목적: 척추 압박골절 환자에서 척추성형술 이후 척추체의 재압박이 발생하는 경우가 증가하고 있다. 이에 척추성형술 시 주입된시멘트의 형상, 무혈성괴사(쿰멜씨병) 여부, 수술의 종류, 골밀도, 성별, 나이 등을 포함한 재압박을 유발 가능한 여러 인자들의 영향을 분석해 보았다. 대상 및 방법: 본 연구는 2005년부터 2015년까지 본원에서 척추 압박골절로 척추성형술 또는 풍선 척추성형술을 시행한 환자를대상으로 단순 방사선 사진 분석을 통해 시멘트의 형상 및 추간판 내 시멘트 유출여부에 대하여 분석하였다. 주입된 시멘트 형상을 척추체 상부 종판에만 또는 하부 종판에만 걸쳐 시멘트가 주입된 경우, 상부 및 하부 종판 모두에 걸쳐 주입되어 있는 경우 및척추체의 가운데에만 주입되어 있는 경우의 총 4가지로 분류하여 각 형상과 재압박골절과의 관계를 분석하였다. 결과: 척추성형술을 시행한 환자 238명 중 59명(24.8%)에서 척추체의 재압박골절이 발생하였다. 압박 골절 당시 무혈성괴사가 동반되어 있던 군에서 그렇지 않은 군에 비해 척추성형술을 시행했음에도 재압박골절이 더 잘 발생하는 것으로 나타났다(p＜0.05). 시술 시 시멘트가 상부 및 하부 종판에 모두에 접촉하며 주입된 경우 재압박골절 발생을 감소시키는 것으로 나타났으며(p=0.008), 풍선 척추성형술을 시행했을 경우 단순 척추성형술을 시행했을 경우보다 척추체 재압박골절 발생이 유의미하게 감소하는 것으로나타났다(p=0.02). 이외에 추간판 시멘트 유출 여부, 시멘트 용량, 성별, 골밀도 등의 인자들은 재압박골절발 생에 영향이 없었다. 결론: 수술 전 무혈성괴사가 확인되었던 경우 척추성형술 후 추시 과정 중에 재압박골절의 발생 여부에 대해 면밀히 평가해야 할것으로 보인다. 또한 주입된 시멘트가 상부 및 하부 종판에 모두 접촉되지 않은 경우 추시 과정 중 재압박골절 발생 여부에 대해세심한 관찰이 필요하며, 시멘트 주입 시 상부 및 하부 종판 모두에 접촉될 수 있게 하기 위한 추가 연구도 필요할 것으로 보인다. Purpose: With the increasing incidence of recompression fractures after vertebroplasty or kyphoplasty, this study analyzed the risk factors that affect the occurrence of recompression vertebral fractures, such as cement distribution, existence of avascular necrosis (Kummell’s disease), type of procedures, bone mineral density, sex, and age. Materials and Methods: Two hundred and thirty-eight patients who underwent vertebroplasty or kyphoplasty at the author’s clinic from 2005 to 2015 were enrolled in this study. The patients were divided into four groups according to the distribution of injected cement. The patients were classified as type 1 and type 2 when injected cement was contacted only to the upper or lower endplate of the body respectively. They were classified as type 3 when both the upper and lower endplates were contacted by injected cement. When neither the upper nor the lower endplate was contacted, the patients were called type 4. This study statistically evaluated the effects of the risk factors, including the cement distribution on the incidence of recompression vertebral fracture after vertebroplasty or kyphoplasty. Results: There were 59 cases (24.8%) of recompression fracture after vertebroplasty or kyphoplasty, among the 238 cases. According to the analysis, the recompression of the vertebral body after vertebroplasty or kyphoplasty occurred more often when the compression fracture was accompanied by osteonecrosis at the body (p<0.05). The patients who had injected cement distributed at both upper and lower plate simultaneously (type 3) had a lower incidence of recompression fracture of the vertebral body after vertebroplasty or kyphoplasty (p=0.008). In addition, the kyphoplasty group had a lower incidence of recompression after the procedure than vertebroplasty group (p=0.02). Conclusion: Careful attention should be given to these patients with osteonecrosis at the compression fracture level through a preoperative evaluation. In addition, if the injected cement does not contact both the upper and lower endplates, careful observation is required during the follow-up period based on the high incidence of vertebral recompression fractures proven through this study. Further technical and biomechanical research and efforts will be needed to make the cement contact both endplates. KCI Citation Count: 0